ChemInform Abstract: Probing Active Surfaces in Solid Oxide Fuel Cells and Electrolysers by Low Energy Ion Scattering (LEIS). Issue 32 (12th August 2014) - Kilner, John; Ishihara, Tatsumi; Druce, John; Tellez, Helena
Abstract: Review: 16 refs.